Studies on multilingual lexicography - Domínguez Vázquez, María José, 1972-; Mirazo Balsa, Mónica; Valcárcel Riveiro, Carlos (Lexicographica. Series maior ;, 2020)
Given the new technological advances and their influence and imprint in the design and development of dictionaries and lexicographic resources, it seems important to put together a series of publications that address this new situation, dealing in particular with multilingual and electronic lexicography in an increasingly digital, multilingual and multicultural society. This is the main objective of this volume, which is structured in two central aspects. In the first of them the concept of multilingual lexicography is discussed in regard to the influence that the Internet and the application of digital technologies have exercised and continue to exercise both in the conception and design of dictionaries and new lexicographic application tools as well as the emergence of new types of users and forms of consultation. The role of the dictionary must necessarily be related to social development and changes. In the second thematic section, different dictionaries and resources that focus on a multilingual and electronic approach to the linguistic data for their lexicographical treatment and consultation are presented.